2008
DOI: 10.1007/s12253-008-9040-1
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of VEGF and MVD, among Patients with Primary Breast Cancer

Abstract: The purpose of the study was to ascertain the value of assessment of vascular endothelial growth factor (VEGF) levels and microvessel density, and to search for correlations between them, in women with breast cancer. The assessment considered factors such as the stage of clinical disease advancement--according to International Union Against Cancer, the grade of histological malignancy, status of axillary lymph nodes and the size of the primary tumour. The concentration of VEGF was assessed in the plasma of 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…When staining intensities were quantified, breast cancer tissues exhibited significantly lower levels of ZNF24 and significantly higher levels of VEGF compared with NATs (supplemental Figure 5). Combined with the findings by Thielemann et al 27 in which increased VEGF levels and microvessel density were found in human breast cancer tissues, our results suggest that ZNF24 may play a negative role in the initiation and/or progression of human breast cancer by inhibiting tumor angiogenesis through regulation of VEGF expression.…”
Section: Levels Of Znf24 and Vegf Are Inversely Correlated In Human Bsupporting
confidence: 86%
“…When staining intensities were quantified, breast cancer tissues exhibited significantly lower levels of ZNF24 and significantly higher levels of VEGF compared with NATs (supplemental Figure 5). Combined with the findings by Thielemann et al 27 in which increased VEGF levels and microvessel density were found in human breast cancer tissues, our results suggest that ZNF24 may play a negative role in the initiation and/or progression of human breast cancer by inhibiting tumor angiogenesis through regulation of VEGF expression.…”
Section: Levels Of Znf24 and Vegf Are Inversely Correlated In Human Bsupporting
confidence: 86%
“…VEGF-A is a member of the VEGF family, and has been confirmed to be a key regulator of angiogenesis. Since the number of newly formed blood vessels within a tumor is usually measured by MVD, both MVD and VEGF-A are good indicators of angiogenesis (Thielemann et al, 2008;Sanaat et al, 2014;Della-Morte et al, 2015). However, the correlation between SIPA1 expression and angiogenesis in gastric tumor tissues was unclear so far.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of scholars [9][10][11][12][13][14] had discussed the relationship between VEGF and MVD in tumors, and most of them believed that the MVD count increased significantly with the increase of the expression of VEGF. In our study, we also find MVD count was higher in VEGF positive group than that in VEGF negative group.…”
Section: Discussionmentioning
confidence: 99%